ANALYSIS OF FINANCIAL MANAGEMENT AND CHALLENGES OF HOUSEHOLD UMKM IN KEMUNING MUDA VILLAGE - Mardiana; Muhammad Fauzan (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2024)
This study aims to describe the real conditions of household businesses in Kemuning Muda Village, Indragiri Hilir Regency. The study was conducted on three household-scale MSME actors, namely producers of tempeh chips, baked cakes, and instant rendang spices. This study used a qualitative descriptive method through semi-structured interviews and direct observation. The results of the study showed that the three business actors faced similar obstacles, including limited capital, local marketing, and the absence of planned business management. There was no business recording system or separation of household and business finances, which made business sustainability difficult. This study can be a basis for designing village MSME empowerment strategies that are in accordance with real needs in the field.